2020
DOI: 10.3390/su12041558
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Yeast Fermentation to Enhance Bioconversion of Coconut Endosperm Waste into Larval Biomass of Hermetia illucens: Statistical Augmentation of Larval Lipid Content

Abstract: The aim of this study was to spur the lipid accumulation by larvae of Hermetia illucens or black soldier fly (BSFL) via feeding with yeast fermented medium. The Saccharomyces cerevisiae, a single cell yeast, was introduced at different concentrations (0.02, 0.1, 0.5, 1.0, 2.5 wt %) to execute an in-situ fermentation on coconut endosperm waste. The rearing of BSFL was started simultaneously and the rearing was stopped once the BSFL reached the fifth instar. With the increasing of yeast concentration, the rearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 29 publications
3
16
2
Order By: Relevance
“…Thus, a low bioconversion of the sediment occurs. The bioconversion of the liquid (4.1-6.6%) is substantially higher than that of previously reported data for municipal sewage sludge (0.2-2.3%) [24] and in the same range as coconut endosperm waste (CEW) (6%) [19] but lower than for fermented CEW (8-11.5%) [19,21]. On the other hand, the bioconversion of the sediment (≤ 0.4%) is in the lower range of municipal sewage sludge (0.2-2.3%) [24], and the bioconversion of both the sediment and the liquid is lower than for food and feed waste (12.8-15.2%) and manure (7.1-11.3%) [24].…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Thus, a low bioconversion of the sediment occurs. The bioconversion of the liquid (4.1-6.6%) is substantially higher than that of previously reported data for municipal sewage sludge (0.2-2.3%) [24] and in the same range as coconut endosperm waste (CEW) (6%) [19] but lower than for fermented CEW (8-11.5%) [19,21]. On the other hand, the bioconversion of the sediment (≤ 0.4%) is in the lower range of municipal sewage sludge (0.2-2.3%) [24], and the bioconversion of both the sediment and the liquid is lower than for food and feed waste (12.8-15.2%) and manure (7.1-11.3%) [24].…”
Section: Discussioncontrasting
confidence: 63%
“…The content of protein and fat in larvae have not been analyzed in this study. However, previous studies on bioconversion of fermented CEW have reported the following values: protein 15-39% [18,20,22] and fat 44-58% [18,21,22]. Analysis of protein and fat in larvae reared on PPBS is recommended for future studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In order to attain lipid-rich BSFL, it was suggested that 1.0 wt% of R. oligosporus should be introduced into CEW and treated by means of ex situ fermentation. As compared with other exo-microbial fermentations, it was found that the highest lipid yield (49%) was also obtained with 1.0 wt% yeast via in situ fermentation (Wong et al, 2020) [38]. For bacterial ex situ fermentation, the employment of 0.02 to 2.5 wt% inoculum sizes resulted in lipid yields falling within the range of 35% to 40% [23].…”
Section: Lipid and Protein Derived From Bsfl Feeding On In Situ And Ementioning
confidence: 98%
“…Helium gas was used as a carrier gas, and the inlet was operated in a split mode (1:50) at a temperature of 250 • C. The column temperature was programmed at the ramping mode. The percentage of FAME composition in BSFL-derived biodiesel was calculated as presented in Equation (5) [40].…”
Section: Transesterification Of Larval Lipid Into Bsfl-based Biodieselmentioning
confidence: 99%